Pengaruh Persepsi Kemudahan, Kemanfaatan dan Kepuasan Nasabah Terhadap Minat Penggunaan Layanan BSI Mobile Banking (Studi Pada Mahasiswa Akuntansi Fakultas Ekonomi dan Bisnis Universitas Islam Malang Angkatan 2019-2022) - Azri, Nur; Mawardi, M. Cholid; Sari, Arista Fauzi Kartika (Universitas Islam Malang, 2024)
A country's financial progress can be seen from the improvement in the money storage industry in that country. The more the account management industry is created, the better the country's financial progress will be. Because financial training is closely related to saving money. Banks are financial educational institutions that are a place for companies, government and private organizations, as well as citizens to store their stores. In a competitive account management situation, banks have to work hard to attract potential customers and retain existing customers. As time went by, improvements in account management began to grow rapidly, many unused banks emerged, one of which was called sharia banks.Keywords: Communication skill, work discipline, quality of human resources, employee performance.